Anti-tumor effect of ultrasound-induced Nordy-loaded microbubbles destruction. (13th September 2016) - Hua, Xing; Ding, Jun; Li, Rui; Zhang, Ying; Huang, Zejun; Guo, Yanli; Chen, Qinghai
Abstract: Background: Synthesized dl-Nordihydroguaiaretic acid (dl-NGDA or "Nordy") can inhibit the growth of malignant human tumors, especially the tumor angiogenesis. However, its liposoluble nature limits its in vivo efficacy in the hydrosoluble circulation of human. Purpose: We tried to use the ultrasonic microbubble as the carrier and the ultrasound-induced destruction for the targeted release of Nordy and evaluate its in vitro and in vivo anti-tumor effect. Methods: Nordy-loaded lipid microbubbles were prepared by mechanical vibration. Effects of ultrasound-induced Nordy-loaded microbubbles destruction on proliferation of human umbilical vein endothelial cells (HUVECs), tumor derived endothelial cells (Td-ECs), and rabbit transplanted VX2 tumor models were evaluated. Results: The ultrasound-induced Nordy-loaded microbubbles destruction inhibited the proliferations of HUVECs and Td-ECs in vitro, and inhibited the tumor growth and the microvasculature in vivo . Its efficacy was higher than those of Nordy used only and Nordy with ultrasound exposure. Conclusion: Ultrasonic microbubbles can be used as the carrier of Nordy and achieve its targeted release with improved anti-tumor efficacy in the condition of ultrasound-induced microbubbles destruction.